Harmful and Potentially Harmful Constituents Analysis of North American ENDS - Smith Cameron; Jamison Brian; Jongsma Candice; Carter Karen; Wang Jiaming; Bates Austin; Ullah Sifat; Cook David; Gene Gillman I. (Contributions to Tobacco and Nicotine Research)
The objective of this study was to create a North American e-cigarette, or electronic nicotine delivery system (ENDS), market map representative of the 2020 and 2021 commercial market for analysis of harmful and potentially harmful constituents (HPHCs) and other chemicals in aerosol. The study consisted of 14 brands (seven closed pod-based, four open (refillable) pod-based, two cigalike, one disposable) and analyzed multiple e-liquid formulations per brand with varying labelled nicotine concentrations and flavors, equating to 35 unique tested ENDS. Aerosol was generated using two puffing regimes (ISO 27068 and intense) and analyzed for primary constituents, metals, carbonyls, and glycidol in a head-to-head comparison in the same testing laboratory. Nicotine yields per puff ranged from 0.045 mg/puff for the lowest yielding ENDS under the ISO 27068 puffing regime to 1.11 mg/puff for the highest yielding ENDS under intense puffing conditions. For carbonyls, all ENDS generated quantifiable amounts of acetaldehyde, acrolein, and formaldehyde in collected aerosol, irrespective of puffing regime, with an increase in yields observed under intense puffing compared to ISO 27068 puffing for the majority of tested ENDS. For metals, the ENDS aerosol yielded nickel (Ni) ranging from below limits of detection (BLOD) to >30 ng/puff, while quantifiable levels of chromium (Cr), copper (Cu), and lead (Pb) were only associated with select ENDS. All tested ENDS aerosol contained quantifiable glycidol ranging from 0.003 to >1.00 µg/puff for ISO 20768 and 0.005 to 1.10 µg/puff for intense puffing regimes. As a category, ENDS aerosol showed significantly reduced levels of HPHCs compared to 1R6F combustible cigarette (CC) smoke on a per nicotine basis. However, there was variability among ENDS and the aerosol of some ENDS products produced increased levels of specific HPHCs (e.g., formaldehyde and nickel) compared to 1R6F CC smoke. The observed HPHC variations appear to be primarily dependent on device design. In summary, this work is one of the most comprehensive analyses of HPHCs for North American ENDS using validated analytical methods in the same test facility for a head-to-head comparison.